A Theoretical Framework for Iterative Synchronization Based on the Sum-Product and the Expectation-Maximization Algorithms - Herzet, C.; Ramon, V.; Vandendorpe, L. (IEEE transactions on signal processing, 2007)
This paper deals with maximum-likelihood (ML) estimation of synchronization parameters for coded transmission systems. In particular, we present a unified framework based on both the sum-product (SP) algorithm and the expectation-maximization (EM) algorithm for the design of iterative synchronizers. The proposed approach is shown to encompass some known iterative synchronizers. In particular, we revisit a previously proposed framework based on the EM algorithm only by means of our "SP-EM" approach. The performance of the proposed synchronization method is assessed in terms of mean-square error and bit-error rate by simulation results. In particular, we consider the joint synchronization of the timing epoch and the carrier phase offset in the case of convolutionally coded and turbo-coded transmissions